Economia do mar : conceito, valor e importância para o Brasil - Carvalho, Andréa Bento (2018)
The concept of a marine economy, its quantification and impacts are important to change or to create appropriate public policies. It is noted that studies dedicated to the economics of the sea in Brazil are still incipient. Therefore, this thesis is dedicated to this interesting and innovative topic of research in Brazil. This thesis presents three essays of Brazilian Marine Economy. The aim of the first essay is to construct a concept of marine economy for Brazil, thus making possible the analysis of the participation of these sectors in the national economy. The Brazilian marine economy was divided into twelve sectors of the economy (sections) making a total of forty activities (classes). The methodology presented for the conceptualization of the Brazilian marine economy incorporates some aspects developed in previous international studies, by classifying the activities directly or indirectly related to the sea. However, it differs from some international studies when considering only activities exclusively developed in states and counties facing the sea. Thus, the Brazilian marine economy is defined as: Economic activities that have direct influence of the sea, including economic activities that do not have the sea as raw material, but which are developed in nearness to the sea. It was verified that the Brazilian marine economy is composed of two hundred and eighty municipalities located in seventeen states and in the three regions - North, Central and South, with the southern coast concentrating the highest indicators of population, GDP and employment in marine activities. The second essay aims to quantify the Brazilian marine economy for 2015 through the estimation of a National Input-Output Matrix which creates the marine sectors by separating activities directly related to the sea, (Marine Dimension activities), as well as indirectly linked to the sea (Adjacent to the Sea). Additionally, it is possible to know the size of the Brazilian marine economy. The result of this work is the Marine Economy Input-Output Matrix, denominated MIP Br Mar. The Brazilian marine economy, for the year 2015, generated for the national economy R$ 1.11 trillion of Gross Domestic Product and R$ 1.18 trillion of Gross Value Added. The Brazilian marine sectors employed more than 19 million people, generating almost R$ 500 billion in wages. The final demand of the marine sectors was estimated at R$ 1.3 trillion. Therefore, it should be noted that the Brazilian marine economy is dominated by the sector of services, where we can highlight tourism. Finally, the third essay presents the backward and forward linkages, in addition to the multipliers of the Brazilian marine economy. For the Marine Dimension, the Sea Manufactures, Marine Living Resources and Maritime Transport sectors have the largest multipliers. Considering the impacts of Backward and Forward policies, the Brazilian marine economy presents, by analyzing the Marine Dimension, two sectors with values greater than 1 for backward linkages (Manufactures of the Sea, both for the open and closed models, and Marine Living Resources for the open model). In relation to forward linkages, a single marine sector, by the marine dimension, presents a value greater than 1 for the open and closed model (Sea Energy). Thus, there are no key sectors in Brazilian marine economy and it is a major consumer of other industries rather than suppliers.